Analisis Penggunaan Virtual Reality (VR) untuk Mengurangi Nyeri dan Kecemasan Selama Persalinan - Aulia, Devy Lestari Nurul; Anjani, Arum Dwi; Oktaviona, Niza; Duriyanti, Duriyanti; Andara, Ireza Fuja; Alini, Alini; Al-Hikmah, Nailah (IAI Nasional Laa Roiba Bogor, 2025)
This study explores the effectiveness of Virtual Reality (VR) as a non-pharmacological method to reduce pain and anxiety during labor. In the context of increasing attention to alternative approaches in pain management, VR is emerging as an innovative solution that has the potential to provide a positive experience for laboring mothers. This quantitative study compared two groups of pregnant women: an intervention group that used VR during labor and a control group that received standard care without the use of VR technology. Data were collected using the visual analog pain scale and STAI anxiety scale before, during, and after labor to measure the effectiveness of the intervention. The results of the analysis showed a significant decrease (p<0.05) in pain and anxiety scores in the VR intervention group compared to the control group. These findings suggest the potential of VR as a promising tool in labor pain and anxiety management, offering a safe and effective approach to improve the labor experience for mothers. Further research with larger samples and more robust designs is needed to confirm these findings and expand understanding of VR applications in the midwifery context.